Bromotrifluoromethane: A Useful Reagent for Hydrotrifluoromethylation of Alkenes and Alkynes - Ren, Yu-Yan; Zheng, Xing; Zhang, Xingang (Synlett, 2018)
Bromotrifluoromethane (CF3Br) is a simple, inexpensive and abundant industrial material employed as a trifluoromethylating reagent. However, only limited strategies using CF3Br as a fluorine source are reported. Herein, we describe a visible-light-induced hydrotrifluoromethylation of alkenes and alkynes with CF3Br. The reaction proceeds under mild conditions with good functional group tolerance, providing a new route for the application of BrCF3 in organic synthesis.
Keywords: bromotrifluoromethane; hydrotrifluoromethylation; alkenes; alkynes; visible-light-induced